Evaluation of in vivo quantification accuracy of the Ingenuity‐TF PET/MR. Issue 10 (14th September 2015) - Maus, Jens; Schramm, Georg; Hofheinz, Frank; Oehme, Liane; Lougovski, Alexandr; Petr, Jan; Platzek, Ivan; Beuthien‐Baumann, Bettina; Steinbach, Jörg; Kotzerke, Jörg; van den Hoff, Jörg
Abstract : Purpose: The quantitative accuracy of standardized uptake values (SUVs) and tracer kinetic uptake parameters in patient investigations strongly depends on accurate determination of regional activity concentrations in positron emission tomography (PET) data. This determination rests on the assumption that the given scanner calibration is valid in vivo . In a previous study, we introduced a method to test this assumption. This method allows to identify discrepancies in quantitative accuracy in vivo by comparison of activity concentrations of urine samples measured in a well‐counter with activity concentrations extracted from PET images of the bladder. In the present study, we have applied this method to the Philips Ingenuity‐TF PET/MR since at the present stage, absolute quantitative accuracy of combined PET/MR systems is still under investigation. Methods: Twenty one clinical whole‐body F18‐FDG scans were included in this study. The bladder region was imaged as the last bed position and urine samples were collected afterward. PET images were reconstructed including MR‐based attenuation correction with and without truncation compensation and 3D regions‐of‐interest (ROIs) of the bladder were delineated by three observers. To exclude partial volume effects, ROIs were concentrically shrunk by 8–10 mm. Then, activity concentrations were determined in the PET images for the bladder and for the urine by measuring the samples in a calibrated well‐counter. In addition, linearity measurements of SUV vs singles rate and measurements of the stability of the coincidence rate of "true" events of the PET/MR system were performed over a period of 4 months. Results: The measured in vivo activity concentrations were significantly lower in PET/MR than in the well‐counter with a ratio of the former to the latter of 0.756 ± 0.060 (mean ± std. dev.), a range of 0.604–0.858, and a P value of 3.9 ⋅ 10 −14 . While the stability measurements of the coincidence rate of "true" events showed no relevant deviation over time, the linearity scans revealed a systematic error of 8%–11% (avg. 9%) for the range of singles rates present in the bladder scans. After correcting for this systematic bias caused by shortcomings of the manufacturers calibration procedure, the PET to well‐counter ratio increased to 0.832 ± 0.064 (0.668 –0.941), P = 1.1 ⋅ 10 −10 . After compensating for truncation of the upper extremities in the MR‐based attenuation maps, the ratio further improved to 0.871 ± 0.069 (0.693–0.992), P = 3.9 ⋅ 10 −8 . Conclusions: Our results show that the Philips PET/MR underestimates activity concentrations in the bladder by 17%, which is 7 percentage points (pp.) larger than in the previously investigated PET and PET/CT systems. We attribute this increased underestimation to remaining limitations of the MR‐based attenuation correction. Our results suggest that only a 2 pp. larger underestimation of activity concentrations compared to PET/CT can be observed if compensation of attenuation truncation of the upper extremities is applied. Thus, quantification accuracy of the Philips Ingenuity‐TF PET/MR can be considered acceptable for clinical purposes given the ±10% error margin in the EANM guidelines. The comparison of PET images from the bladder region with urine samples has proven a useful method. It might be interesting for evaluation and comparison of the in vivo quantitative accuracy of PET, PET/CT, and especially PET/MR systems from different manufacturers or in multicenter trials.